Electrochemical Method for Wastewater Treatment of Textile Production Enterprises by Electrocoagulation - I., Mavlanova Yu.; M., Xolov F. (European Journal of Life Safety and Stability (2660-9630), 2021)
This research originally attempts to highlight the significance of electrode as one of the alternative method to conventional chemical coagulation, electrocoagulation has received widespread recognition for the intelligent technique which effectively remove the pollutant in wastewater. Electrocoagulation has proven to be simple, affordable and efficient to treat highly polluted wastewater. Another advantage of using electrocoagulation is this process is easy to operate, involved in simple equipment, offered a short retention time and required a small space which contributes to low operating costs in industrial applications as compared to conventional ponding system or chemical coagulation.